Development of performance evaluation indicators for social enterprises: the use of Delphi technique - Taušl Procházková, Petra; Nosková, Marta; Machová, Kristýna; Velíšková, Veronika (Journal of Business Economics and Management, 2021)
Social enterprises have become a natural part of the economy. Their importance is significantly increasing, as well as the need to evaluate their performance. There are different points of view on the indicators and methods used to evaluate their performance and they often lack simplicity and are costly and time consuming. Thus, this study aims to identify and discuss performance evaluation indicators for social enterprises with particular focus on identifying a set of indicators that might be applied without placing high demands on each social enterprise. A two-phase approach was adopted and applied in the Czech social entrepreneurship environment. First, the Delphi technique was used to get a set of indicators for each of the areas of the triple bottom line principles. Consequently, an empirical examination of these indicators using a set of social enterprises was conducted. Final results were determined using Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). As a result, a set of twelve indicators that cover social, economic, environmental and local areas are proposed. These indicators reflect the opinions of experts in the field as well as their practical usefulness, which is discussed at the end of the paper.